Stressful life events and depressive symptoms among adolescents in Malaysia: the mediating role of maladaptive cognitive schema - Wong, Yi Shan; Zulkefly, Nor Sheereen; Tan, Kit-Aun (Walter de Gruyter GmbH, 2020)
Objectives: The present study aimed to examine the mediational role of maladaptive cognitive schema in the association between stressful life events, which are operationalised as major (i. e. negative life events) and minor (i. e. daily hassles) life stressors, and depressive symptoms among adolescents.